Use of IgE and IgG4 epitope binding to predict the outcome of oral immunotherapy in cow's milk allergy. Issue 3 (6th January 2014) - Savilahti, Emma M.; Kuitunen, Mikael; Valori, Miko; Rantanen, Ville; Bardina, Ludmilla; Gimenez, Gustavo; Mäkelä, Mika J.; Hautaniemi, Sampsa; Savilahti, Erkki; Sampson, Hugh A.
Abstract Background Oral immunotherapy (OIT) with cow's milk (CM) has been reported to induce a number of specific antibody responses, but these remain to be fully characterized. Our objective was to explore whether IgE and IgG4 epitope binding profiles could predict the risk of side effects during CM OIT. Methods The study population consisted of 32 children (6–17 yr of age) with CM allergy: 26 children who successfully completed OIT and six children who discontinued therapy due to adverse reactions. We investigated sera drawn before and after OIT. We analyzed specific IgE and IgG4 binding to CM protein‐derived peptides with a microarray‐based immunoassay. Antibody binding affinity was analyzed with a competition assay where CM proteins in solution competed with peptides printed on the microarray. Results IgE binding to CM peptides decreased and IgG4 binding increased following the OIT in children who attained desensitization. Compared with children who successfully completed OIT, those who discontinued OIT due to adverse reactions developed increased quantities and affinity of epitope‐specific IgE antibodies and a broader diversity of IgE and IgG4 binding, but less overlap in IgE and IgG4 binding to CM peptides. Conclusions Detailed analysis of IgE and IgG4 binding to CM peptides may help in predicting whether CM OIT will be tolerated successfully. It may thus improve the safety of the therapy.